Improving Service Quality as an Effort to Grow Customer Loyalty - Pinta Nailah Lubis; Muhammad Fauzan Azhmy (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to analyze the effect of service quality on customer loyalty. Service quality uses the dimensions of tangible, reliability, responsiveness, assurance, and empathy. The data used are primary data and secondary data. Primary data was collected through questionnaires distributed to employees, while secondary data was obtained from documentation studies obtained from various information held by the company and the results of previous research. The data analysis method uses quantitative methods, namely Multiple Linear Regression analysis. The population in this study were customers of Bank Panin Dubai Syariah Medan. The sample in this study was 92 respondents. The results showed that tangible, reliability, responsiveness, assurance, and empathy had a positive and significant effect either partially or simultaneously. While the ability of tangible, reliability, responsiveness, assurance, and empathy explain customer loyalty is 52.90% while the remaining 47.10% is explained by other variables that are not included in this research model.